How to attract applicants in the atlantic versus the asia-pacific region? A cross-national analysis on China, India, Germany, and Hungary. - Baum, M; Kabst, Rüdiger (Journal of World Business (JWB).)

Bootstrapping Skynet: Calibration and Autonomic Self-Control of Structured Peer-to-Peer Networks - Graffi, Kalman; Klerx, Timo (Proceedings of the International Conference on Peer-to-Peer Computing (P2P'13))
Peer-to-peer systems scale to millions of nodes and provide routing and storage functions with best effort quality. In order to provide a guaranteed quality of the overlay functions, even under strong dynamics in the network with regard to peer capacities, online participation and usage patterns, we propose to calibrate the peer-to-peer overlay and to autonomously learn which qualities can be reached. For that, we simulate the peer-to-peer overlay systematically under a wide range of parameter configurations and use neural networks to learn the effects of the configurations on the quality metrics. Thus, by choosing a specific quality setting by the overlay operator, the network can tune itself to the learned parameter configurations that lead to the desired quality. Evaluation shows that the presented self-calibration succeeds in learning the configuration-quality interdependencies and that peer-to-peer systems can learn and adapt their behavior according to desired quality goals.

Gender Effects on Entrepreneurial Intention: A Meta-Analytical Structural Equation Model. - Haus, I; Steinmetz, Holger; Isidor, R; Kabst, Rüdiger (International Journal of Gender and Entrepreneurship (IJGE))

Analyzing observed composite differences across groups: Is partial measurement invariance enough? - Steinmetz, Holger (European Journal of Research Methods for the Behavioral and Social Sciences.)

Beschleunigung von Tiefenberechung aus Stereobildern durch FPGA-basierte Datenflussrechner - Bick, Christian

Bandbreiten-beschränktes Scheduling mit skalierbaren Jobanforderungen in Multiprozessor-Umgebungen - Meschede, Julian

Automated Service Composition for On-the-Fly SOAs - Huma, Zille; Gerth, Christian; Engels, Gregor; Juwig, Oliver (Proceedings of the 11th International Conference on Service Oriented Computing (ICSOC'13))
In the service-oriented computing domain, the number of available software services steadily increased in recent years, favored by the rise of cloud computing with its attached delivery models like Software-as-a-Service (SaaS). To fully leverage the opportunities provided by these services for developing highly flexible and aligned SOA, integration of new services as well as the substitution of existing services must be simplified. As a consequence, approaches for automated and accurate service discovery and composition are needed. In this paper, we propose an automatic service composition approach as an extension to our earlier work on automatic service discovery. To ensure accurate results, it matches service requests and available offers based on their structural as well as behavioral aspects. Afterwards, possible service compositions are determined by composing service protocols through a composition strategy based on labeled transition systems.

Auktionen im Beschaffungsmanagement - Eine spieltheoretische Analyse - Meckenstock, Kevin

Attributbasierte Verschlüsselung mittels Gittermethoden - Mathematische Grundlagen, Verfahren und Sicherheitsbeweise - Kohn, Kathlén

Asymmetric Nash bargaining solutions and competitive payoffs - Brangewitz, Sonja; Gamp, Jan-Philip (Economics Letters)
We establish a link between cooperative and competitive behavior. For every possible vector of weights of an asymmetric Nash bargaining solution there exists a market that has this asymmetric Nash bargaining solution as its unique competitive payoff vector.

Approximation Algorithms for the Linear Arrangement of Special Classes of Graphs - Setzer, Alexander

Analyse von Benutzeranforderungen von Service-Kompositionen mittels Modelchecking - Nickel, Tobias

An Approach for a Decision Support Systems to optimize Water Tanks in Water Supply Systems by combining Network Reduction, Optimization and Simulation - Hallmann, Corinna
Since the last two decades, the water consumption in Germany is decreasing, which causes the water tanks and pipes in a water supply system to work inefficiently. This paper proposes an approach for a decision support system, which helps to decide how to plan new water tanks and resize existing tanks in water supply systems. The approach uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a nonconvex Mixed Integer Quadratically Constrained Program (MIQCP), which is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computational times, the size of the water supply system model is reduced before building the optimization model. By applying several network reduction techniques there may occur some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water supply system, the solution is verified by a hydraulic simulation tool.

Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Decision Modeling for Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (Proceedings of the 46th Hawaii International Conference on System Science)

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, Philip; Graffi, Kalman (Proceedings of the Conference on Networked Systems (NetSys))
Distributed hash tables are very versatile to use, as distributed storage is a desirable feature for various applications. Typical structured overlays like Chord, Pastry or Kademlia consider only homogeneous nodes with equal capacities, which does not resemble reality. In a practical use case, nodes might get overloaded by storing popular data. In this paper, we present a general approach to enable capacity awareness and load-balancing capability of homogeneous structured overlays. We introduce a hierarchical second structured overlay aside, which allows efficient capacity-based access on the nodes in the system as hosting mirrors. Simulation results show that the structured overlay is able to store various contents, such as of a social network, with only a negligible number of overloaded peers. Content, even if very popular, is hosted by easily findable capable peers. Thus, long-existing and well-evaluated overlays like Chord or Pastry can be used to create attractive DHT-based applications.

A Survey of Fuzzy Service Matching Approaches in the Context of On-The-Fly Computing - Platenius, Marie; von Detten, Markus; Becker, Steffen; Schäfer, Wilhelm; Engels, Gregor (Proceedings of the 16th International ACM Sigsoft Symposium on Component-Based Software Engineering)
In the last decades, development turned from monolithic software products towards more flexible software components that can be provided on world-wide markets in form of services. Customers request such services or compositions of several services. However, in many cases, discovering the best services to address a given request is a tough challenge and requires expressive, gradual matching results, considering different aspects of a service description, e.g., inputs/ouputs, protocols, or quality properties. Furthermore,in situations in which no service exactly satifies the request, approximate matching which can deal with a certain amount of fuzziness becomes necessary. There is a wealth of service matching approaches, but it is not clear whether there is a comprehensive, fuzzy matching approach which addresses all these challenges. Although there are a few service matchingsurveys, none of them is able to answer this question. In this paper, we perform a systematic literature survey of 35 (outof 504) service matching approaches which consider fuzzy matching. Based on this survey, we propose a classication,discuss how different matching approaches can be combined into a comprehensive matching method, and identify future research challenges.

A privacy-friendly Architecture for future Cloud Computing - Petrlic, Ronald; Sekula, Stephan; Sorge, Christoph (International Journal of Grid and Utility Computing)
We present a privacy-friendly architecture for a future cloud computing scenario where software licensing and software payment plays a major role. We show how digital rights management as a technical solution for software licensing can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers and execute it at computing centres stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and that their validity is checked before execution. Thus, DRM constitutes an incentive for software providers to take part in such a future cloud computing scenario. We employ a software re-encryption scheme so that computing centres are not able to build profiles of their users – not even under a pseudonym. We make sure that malicious users are unable to relay software to others.

A Local Heuristic for Latency-Optimized Distributed Cloud Deployment - Keller, Matthias; Pawlik, Stefan; Pietrzyk, Peter; Karl, Holger (Proceedings of the 6th International Conference on Utility and Cloud Computing (UCC) workshop on Distributed cloud computing)
In Distributed Cloud Computing, applications are deployed across many data centres at topologically diverse locations to improved network-related quality of service (QoS). As we focus on interactive applications, we minimize the latency between users and an application by allocating Cloud resources nearby the customers. Allocating resources at all locations will result in the best latency but also in the highest expenses. So we need to find an optimal subset of locations which reduces the latency but also the expenses – the facility location problem (FLP). In addition, we consider resource capacity restrictions, as a resource can only serve a limited amount of users. An FLP can be globally solved. Additionally, we propose a local, distributed heuristic. This heuristic is running within the network and does not depend on a global component. No distributed, local approximations for the capacitated FLP have been proposed so far due to the complexity of the problem. We compared the heuristic with an optimal solution obtained from a mixed integer program for different network topologies. We investigated the influence of different parameters like overall resource utilization or different latency weights.